Exploring the association between genetic variation in the SUMO isopeptidase gene USPL1 and breast cancer through integration of data from the population-based GENICA study and external genetic databases - Lorenzo Bermejo, Justo; Kabisch, Maria; Dünnebier, Thomas; Schnaidt, Sven; Melchior, Frauke; Fischer, Hans-Peter; Harth, Volker; Rabstein, Sylvia; Pesch, Beate; Brüning, Thomas; Justenhoven, Christina; Brauch, Hiltrud; et al. (International journal of cancer, 2013)
Small ubiquitin-like modifier (SUMO) proteins are covalently attached to target proteins to modify their function. SUMO conjugation participates in processes tightly linked to tumorigenesis. Recently USPL1 (ubiquitin-specific peptidase-like (1) was identified as a SUMO isopeptidase. We report here on the first exploratory study investigating the relationship between genetic variability in USPL1 and breast cancer. Three potentially functional nonsynonymous coding SNPs (rs3742303, rs17609459, rs7984952) were genotyped in 1,021 breast cancer cases and 1,015 controls from the population-based GENICA study. We took advantage of multiple genotype imputation based on HapMap and the 1000 Genomes Project data to refine the association screening in the investigated region. Public genetic databases were also used to investigate the relationship with USPL1 expression in lymphoblastoid cell lines and breast tissue. Women homozygous for the minor C allele of rs7984952 showed a lower risk of Grade 3 breast tumors compared to TT homozygotes (OR 0.50, 95% CI 0.30-0.81). Case-only analyses confirmed the association between rs7984952 and tumor grade (OR 0.60, 95% CI 0.39-0.93). Imputation results in a 238 kb region around rs7984952 based on HapMap and the 1000 Genomes Project data were similar. No imputed variant showed an association signal stronger than rs7984952. USPL1 expression in tumor breast tissue increased with the number of C alleles. The present study illustrates the contribution of multiple imputation of genotypes using public data repositories to standard genotyping laboratory. The provided information may facilitate the design of independent studies to validate the association between USPL1 rs7984952 and risk of Grade 3 breast tumors.
Gesehen am 24.11.2020